Specificity and function of T cell subset identities using single‐cell sequencing - Xuanqi Liu; Zhenhua Zhu; Xiangdong Wang (Wiley, 2023)
Abstract T cells, with numerous classifications, are vital components of the adaptive immune system, which function to maintain homeostasis to protect against pathogens. With the rapid development of single‐cell RNA sequencing (scRNA‐seq), the specificity and functions of high‐resolution characterizations and identities of T cells are continuously explored and discovered. The exact T cell identities provide new insights for deeply understanding the heterogeneity of T cells and for the identification of previously unrecognized cell subsets. The accuracy and specificity of T cell cluster and annotation are critical and important in scRNA‐seq analyses, even though the characters and numbers of T cell marker gene panels (MGPs) are to be furthermore improved and uncovered. In order to initiate the discussion on identities of T cell subsets/clusters and impacts of identity specificity in the understanding of immune function, the present review systematically summarized the T cell identities of MGPs and functional characteristics of distinct T cell identities in the scRNA‐seq analysis. We also discussed the critical gene differences among panels across T cell subsets, cell functional states, tissue types, and diseases, with a special focus on the significance and potential values of T cell MGP accuracy and specificity in clinical applications. We hope that the precise knowledge of T cell subsets/clusters benefit decision designs and makings of biomarker discoveries and therapeutic strategies to improve the outcomes of patients.